Research in human subjetcs: ethical aspects and the state of art in Brazil - Souza e Azêvedo, Eliane Elisa de; Gomes, Maria da Glória S. (SITIENTIBUS série Ciências Biológicas, 2002)
The ethics of research in human subjects is discussed on its historical aspects, guiding documents and conflicts of interest in certain areas. In Brazil, the Resolutions 196/96 from the National Health Commission, Ministry of Health is the main guiding document. The National Commission on Research Ethics centers in Brasilia a national wide net of about 400 Committees on Research Ethics all over the country. The State University of Feira de Santana in the State of Bahia has its own Committee of Research Ethics since 2001. The experience of this Committee, similarly to many others in Brazil, points towards the necessity of giving special training to the researchers regarding the elaboration of the term of consent. The Authors suggest that throughout workshops is the best way for giving this type of training.